Return To Bali: Uncovering The Drivers Of Repeat Visits In A Changing Tourism Landscape - Gunawan, Ni Putu Risma Febi; Ni Made Prasiwi Bestari (Pusat Riset dan Inovasi Nasional, 2026)
This study investigates the determinants of tourists’ revisit intentions to Bali by examining the roles of destination image, push motivation, pull motivation, and tourist satisfaction. Using a quantitative explanatory approach, data were collected from 220 domestic and international tourists who had visited Bali at least twice. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that pull motivation has the strongest positive influence on both tourist satisfaction and revisit intention, indicating that external factors such as destination attractiveness, facilities, and natural beauty play a crucial role in encouraging repeat visits. Destination image also significantly affects tourist satisfaction, which in turn mediates its relationship with revisit intention. However, push motivation shows no significant effect on either satisfaction or revisit intention. These results highlight the importance of maintaining destination quality and positive visitor experiences to foster long-term tourist loyalty. The study contributes to a better understanding of how motivational and perceptual factors interact to shape revisit behavior in the context of Bali’s evolving tourism landscape.